Prior immunity to Ureaplasma urealyticum protects against respiratory infection in immunosuppressed mice - Maha Y. Al-Jabri; Robin Patel; Derek Fleming (Microbiology Spectrum)
ABSTRACT Ureaplasma species can cause systemic infections in immunocompromised hosts, including lung transplant recipients. Here, we investigated the impact of prior exposure to Ureaplasma urealyticum on the risk of U. urealyticum and Ureaplasma parvum infection in mice subjected to an immunosuppression regimen similar to that administered to solid organ transplant recipients. Mice were immunized with three intramuscular injections of U. urealyticum, with control mice injected with adjuvant only. Following immunization, mice received tacrolimus, mycophenolate mofetil, and methylprednisolone, and then were challenged with U. urealyticum or U. parvum intraperitoneally and intratracheally over 6 days. Relative U. urealyticum antibody levels in plasma were assessed over time, and lungs were harvested at sacrifice for bacterial load quantification, assessed using a color-changing unit assay. U. urealyticum antibody levels were higher in immunized compared with control animals (P < 0.0001), even when animals were immunosuppressed. U. urealyticum and U. parvum lung burden was reduced in immunized compared with control mice (~6 log10 reduction for U. urealyticum and <1 log10 reduction for U. parvum; P = 0.008 and 0.046, respectively). In summary, this study shows that prior exposure to live U. urealyticum provides some protection against infection with U. urealyticum.IMPORTANCEUreaplasma-induced hyperammonemia syndrome is a rare but potentially deadly complication of solid organ transplantation, especially lung transplantation. The pathophysiology of this relatively recently recognized condition is poorly understood, and it is unclear what factors may influence patient susceptibility. This study investigates the possible protective effects of prior exposure to Ureaplasma urealyticum in a mouse model subjected to an immunosuppression regimen similar to that given to lung transplant recipients. The findings show that prior exposure could provide protection against Ureaplasma lung infection.